A decision support system for the reading of ancient documents - Roued-Cunliffe, H (2011)
The research presented in this thesis is based in the Humanities discipline of Ancient History and begins by attempting to understand the interpretation process involved in reading ancient documents and how this process can be aided by computer systems such as Decision Support Systems (DSS). The thesis balances between the use of IT tools to aid Humanities research and the understanding that Humanities research must involve human beings. It does not attempt to develop a system that can automate the reading of ancient documents. Instead it seeks to demonstrate and develop tools that can support this process in the five areas: remembering complex reasoning, searching huge datasets, international collaboration, publishing editions, and image enhancement. This research contains a large practical element involving the development of a DSS prototype. The prototype is used to illustrate how a DSS, by remembering complex reasoning, can aid the process of interpretation that is reading ancient documents. It is based on the idea that the interpretation process goes through a network of interpretation. The network of interpretation illustrates a recursive process where scholars move between reading levels such as ‘these strokes look like the letter c’ or ‘these five letters must be the word primo’. Furthermore, the thesis demonstrates how technology such as Web Services and XML can be used to make a DSS even more powerful through the development of the APPELLO word search Web Service. Finally, the conclusion includes a suggestion for a future development of a working DSS that incorporates the idea of a layer-based system and focuses strongly on user interaction.